2017
DOI: 10.1007/s00167-017-4508-8
|View full text |Cite
|
Sign up to set email alerts
|

The forgotten joint: quantifying the anatomy of the proximal tibiofibular joint

Abstract: The ligament bundles of the proximal tibiofibular joint were reproducibly identified between specimens in relation to surrounding bony landmarks. Up to four bundles were identified in the anterior ligament complex and up to three in the posterior complex. Variation in bundle orientation and footprint size was observed. Based on these findings, an anatomic reconstruction can be performed using surrounding reliable landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…However, the method used for data collection has been demonstrated to be highly repeatable. 2,15 Two board-certified orthopaedic surgeons with experience in anatomic dissections performed all the dissections and data collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the method used for data collection has been demonstrated to be highly repeatable. 2,15 Two board-certified orthopaedic surgeons with experience in anatomic dissections performed all the dissections and data collection.…”
Section: Discussionmentioning
confidence: 99%
“…The fibular head is pyramidal in shape and has three anatomical areas, the articular surface for the tibia, the fibular styloid and the lateral tubercle. The lateral tubercle of the fibular head is the site of the attachment of the fibular collateral ligament [36,37]. On the medial side of the knee, the superficial medial collateral ligament has one femoral attachment and two tibial attachments.…”
Section: The Anatomy Of the Proximal Tibiamentioning
confidence: 99%
“…Anavian et al. 13 performed an anatomic study and reported that an approximation for the center points of the posterior ligaments should be placed on the posteromedial aspect of the fibular styloid. Relative to these locations, a fluoroscopic study by Marchetti et al.…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, anatomic reconstructions have become the most weighted priority for restoring stability, and intraoperative fluoroscopy can be used for ensuring correct tunnel placement for subsequent orientation of the posterior PTFJ structures. Anavian et al 13 . performed an anatomic study and reported that an approximation for the center points of the posterior ligaments should be placed on the posteromedial aspect of the fibular styloid.…”
Section: Discussionmentioning
confidence: 99%